Social Media Marketing Dominates 2019 Research Trends: Pemasaran Media Sosial Mendominasi Tren Riset 2019 - Ghafiansya, Firdan Isya; Afifah, Jihan Alifia; Berlina, Yusita Setya; Abadi , Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates publication trends on the use of technology and social media in marketing strategies from 2013 to 2023 using Crossref index data and VOSviewer software. Data from scientific articles indexed by Crossref were collected using Publish or Perish (PoP) software and analyzed for keyword mapping. Results showed that 2019 had the highest number of publications, with